Maize root architecture and water stress tolerance: an approximation from crop models - Carretero, Ramiro (2014)
This work presents an assessment of potential advantages of drought tolerance in maize (Zea mays L.) production. A higher water uptake resulting from an enhanced root exploration at deep soil layers seems to be the most promising mechanism. The potential field-level impacts of this mechanism is assessed in two contrasting agroecological areas of the Argentine Pampas using the CERES-Maize model. The soil root growth factor parameter (SRGF) was manipulated to represent a modified maize hybrid with higher density of deep roots. Enhanced root exploration increased maize transpiration and consequently biomass production and yields. Benefits of the modified hybrid tend to be higher under low water availability conditions (low soil water content at sowing and/or rains during crop cycle). Although higher yield responses to root architecture changes were initially expected in the marginal semiarid area (Pilar), the opposite was observed: the average yield increases were 4.7 and 11.7% for Pilar and Pergamino, respectively. The modified hybrid showed lower yields than the current one in approximately 10% of the simulated situations. There were no yield penalties for the modified hybrid in cropping cycles with high water availability. This work shows strong interactions between root architecture and the environmental conditions in which crops are grown that affect potential field-level benefits. We highlight the need for assessing attributes tied to drought tolerance in the context of agroecological conditions in which plants will be grown to identify which drought-tolerance mechanisms might prove effective under different water-stress conditions.